2018
DOI: 10.1007/s10936-018-9571-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Iranian ELT Context-Specific Grit Instrument

Abstract: Grit as an interesting and significant topic in psychology has been associated with better study habits and higher grades through perseverance and passion for long term goals. The only available measurement instrument of grit (Duckworth et al. in J Personal Soc Psychol 92:1087-1101, 2007) is general both in terms of its subject matter and context. Thus, this study aims to develop and validate an English as a foreign language (EFL) grit instrument whose items are specific to EFL context to obtain a more detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Findings showed that none of the grit subscales were related to vocabulary reading test, however, a positive relation was found between COI and vocabulary test. Ebadi et al (2018) developed an L2-specific grit scale with 26 items. After running exploratory factor analysis and confirmatory factor analysis, researchers came up with a four-factor model of L2 grit with 15 items.…”
Section: Grit In Second Language Acquisition Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings showed that none of the grit subscales were related to vocabulary reading test, however, a positive relation was found between COI and vocabulary test. Ebadi et al (2018) developed an L2-specific grit scale with 26 items. After running exploratory factor analysis and confirmatory factor analysis, researchers came up with a four-factor model of L2 grit with 15 items.…”
Section: Grit In Second Language Acquisition Researchmentioning
confidence: 99%
“…These two noncognitive factors have recently attracted the attention of L2 researchers (Banse & Palacios, 2018;Ebadi et al, 2018;Feng & Papi, 2020;Lou & Noels, 2017a;Mercer & Ryan, 2009;Sudina & Plonsky, 2020;Teimouri et al, 2020;Wei et al, 2019), though the number of studies is scant and further research is required to deepen our understanding of the role of these two factors in L2 learning context. Several studies have indicated that people with different language mindsets have different goals for language learning and experience different levels of anxiety (Lou & Noels, 2016, 2017a.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, school-specific grit incrementally predicts academic achievement beyond the influence of domain-general grit and gender (Cormier et al, 2019). Other researchers have developed and validated domain-specific grit scales for foreign language learning (Ebadi et al, 2018). Yet, it is evident that except for the study of Ebadi et al (2018), existing studies primarily focused on the consequences of domain-specific grit in Western societies (e.g., United States).…”
Section: Designing Alternative Conceptualizations and Measures Of Gritmentioning
confidence: 99%
“…Other researchers have developed and validated domain-specific grit scales for foreign language learning (Ebadi et al, 2018). Yet, it is evident that except for the study of Ebadi et al (2018), existing studies primarily focused on the consequences of domain-specific grit in Western societies (e.g., United States). Addressing this methodological grit entails exploring the role of domainspecific grit in non-Western and collectivist contexts to provide evidence about the cross-cultural applicability of grit in various cultural settings.…”
Section: Designing Alternative Conceptualizations and Measures Of Gritmentioning
confidence: 99%
“…As a result, mastery of the role of grit deals with new standpoints for higher teaching supervisors when bearing in mind the students’ academic presentation. Grit is a disposition attribute that can be fostered and taught to scholars ( Ebadi et al, 2018 ). Higher academic administrators can improve grit in students by providing chances to undertake long-term purposes worthy of learners’ determination and providing a demanding and compassionate setting to accomplish their objectives.…”
Section: Implications and Future Directionsmentioning
confidence: 99%